DETECTING FINANCIAL STATEMENT FRAUD USING FRAUD DIAMOND (A Study on Banking Companies Listed On the Indonesia Stock Exchange Period 2012-2016) - Rizqa Syahria (Association of Certified Fraud Examiners Indonesia Chapter, 2019)
Financial statement fraud is one type of fraud that causesmore adverse effect than other types of fraud. Based on this phenomenon, this study aims to detect financial statement fraud using fraud diamond. There are four factors that encourage a person to commit fraud; pressure, opportunity, rationalization and capability. The dependent variable used in this study was financial statement fraud and the independent variables used were financial stability, external pressure, financial target (pressure), external auditor quality (opportunity), change in auditor (rationalization), and change of directors (capability). This study employed quantitative research approach. The population wasthe entire banking companies listed on the Stock Exchange in the period of 2012-2016. Sampling was conducted using purposive sampling method and acquired a sample of 19 banking companies. Data analysis was conducted using a logistic regression analysis with SPSS 16 software. The results showthat financial stability and change in auditors have an effect on financial statement fraud. However, external pressure, financial target (pressure), external auditor quality (opportunity), and change of directors (capability) have no effect on financial statement fraud.